LEVEL OF FETUIN-A, ENDOTHELIN-1 AND SEX HORMONES IN SERUM OF ISOLATED SYSTOLIC HYPERTENSIVE PATIENTS - Alqasim, Abdulmonim (Pakistan Journal of Physiology, 2018)
Background: Arterial stiffness is characterised by isolated systolic hypertension (ISH). Factors such as Fetuin-A, Endothelin-1 (ET-1), Testosterone (TEST), and Progesterone (PROG) have been demonstrated to be involved in arterial stiffness. If changes in blood level of these parameters are detected in ISH and hypertensive patients, it can reflect their expression, production, and association with the pathophysiology of these diseases. Since this association of ISH and hypertension (HTN) with above mentioned factors is still not clear, the present study was carried out for their identification in such diseases. Methods: Serum level of these parameters was measured through ELISA in three groups: (I) ISH patients (n=9), (II) hypertensive patients (n=7), and (III) normal subjects (n=7). Results: Significantly reduced levels of Fetuin-A (0.17±0.03 ηg/ml, n=39) were observed in ISH (p<0.05) without significant changes in TEST (19.2±1.9, n=15), PROG (0.72±0.2, n=19), and ET-1 (0.09±0.02, n=30) levels compared to normal subjects. However, in HTN, increased ET-1 (0.2±0.03, n=14, p<0.05) and decreased TEST (8.125±1.8, n=9, p<0.05) with non-significant changes in Fetuin-A (0.29±0.06, n=18) and PROG (0.67±0.3, n=7) levels have been observed. Conclusion: Low levels of Fetuin-A, in ISH suggests its possible contribution in the pathophysiology of arterial stiffness and subsequently causing increase in systolic blood pressure. An increase in the (ET-1) endothelin-1, and decrease in TEST in hypertensive patients suggests their possible involvement in physiology and pathophysiology of these vascular diseases. These findings open new avenues for further studies regarding pathophysiology of ISH and HTN that may lead to finding a better treatment for these diseases.